Thiopurine metabolite level and toxicity in Indians with inflammatory bowel disease - Parkar, Suruchi P (JGH Open, 2017)
BACKGROUND AND AIM: A lower dose requirement and higher toxicity of thiopurine is reported in Asian patients with inflammatory bowel disease (IBD) as compared with Caucasian patients. These reports are based on thiopurine methyltransferase measurement studies rather than metabolite estimation. We studied the utility of thiopurine metabolite estimation in Indian patients with IBD and compared dose and toxicity with Asian and Caucasian patients. METHODS: In this prospective study, 6‐thioguanine nucleotide (6‐TGN) and 6‐methylmercaptopurine levels were determined by HPLC in 76 IBD patients treated with thiopurines. The levels were correlated with dose, disease activity, and toxicity. The dose‐related metabolite levels and toxicity were compared with Caucasian and Asian patients reported in literature. RESULTS: Of the 76 patients (32 women, mean age: 35.9 [SD: 14.54] years, 36 Crohn's disease and 40 ulcerative colitis), 1 non‐compliant patient had undetectable level of metabolites. Of the 75 patients, 21(28%) had therapeutic level of 6‐TGN, 37(49%) had subtherapeutic level and 17(23%) had supratherapeutic level. The 6‐methylmercaptopurine levels ranged up to 4971 pmol/8 × 10(8) red blood cells. Six (8%) patients showed toxicity. Thiopurine dose was optimized in 20 (26.31%) patients. Dose‐based metabolite levels were comparable to Asian and Caucasian patients. The toxicity (8%) observed in our patients was less than that reported (12–39%). CONCLUSION: Half of the patients in this study had low and a quarter had high 6‐TGN levels. One‐fourth of the patients needed dose modification. The dose‐based metabolite levels were comparable and the toxicity was less than that reported in Asian and Caucasian patients.